2018
DOI: 10.1021/acs.analchem.8b02553
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodinated Pentixather for SPECT Imaging of Expression of the Chemokine Receptor CXCR4 in Rat Myocardial-Infarction–Reperfusion Models

Abstract: The purpose of this study is to develop a specific CXCR4-targeting radioiodinated agent (I- or I-pentixather) for single-photon-emission-computed-tomography (SPECT) imaging of CXCR4 expression in myocardial-infarction-reperfusion (MI/R) rat models. After SPECT-CT imaging withI-pentixather at 4, 12, and 36 h and 3 and 7 days after MI/R, the models were validated by ex vivo autoradiography, TTC staining, and immunohistochemistry and in vivo echocardiography and classical Tc-MIBI perfusion imaging. The SPECT-CT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…published data. 23,27 Thackeray et al reported a significantly increased I/R at day 3 as compared to the control group with a significant decline up to day 7. 23 Li et al investigated the CXCR4 expression in a rat ischemiareperfusion model (I/R) with 125 I-pentixather and found a maximum uptake 3 days after I/R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…published data. 23,27 Thackeray et al reported a significantly increased I/R at day 3 as compared to the control group with a significant decline up to day 7. 23 Li et al investigated the CXCR4 expression in a rat ischemiareperfusion model (I/R) with 125 I-pentixather and found a maximum uptake 3 days after I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Signal decreased after 3 days but was still visible 7 days after MI. 27 However, with our PET imaging approach, the exact source of the cellular signal remains unclear. In fact, the image displays a composition of different cell types, which are present in the respective myocardial region.…”
Section: Discussionmentioning
confidence: 99%
“…Saturation binding experiments were performed by using PR‐positive MCF‐7 cells according to the published procedures . There were approximately 2 × 10 5 cells in each well of a 24‐well plate to which eight different concentrations of 131 I‐EIPBA or 131 I‐EIPB were used, ranging from 1 to 150 nmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…CXCR4 plays a pivotal role in recruiting immune cells and homing stem cells and progenitor cells 182-184. CXCR4 is overexpressed on multiple human tumor types including esophageal, prostate, ovarian, and renal cell carcinoma, boosting tumor proliferation and metastasis 185, 186.…”
Section: Small Molecules For Imaging Cancer Immunotherapymentioning
confidence: 99%